Time for Change: The Normalization of Corruption and Diversion in the Humanitarian Sector - Jackson, Ashley; Majid, Nisar (My University, 2024)
This paper explores aid diversion and corruption. It argues that, although the aid sector often treats corruption and diversion as an anomaly, they are pervasive, systemic and often unwittingly perpetuated by standard aid sector practices. Drawing primarily on evidence from Somalia and Afghanistan (with reference to other contexts), this paper explores the specific aid practices that enable and perpetuate corruption and diversion, and what donors and implementers should be doing differently. Through the lens of Somalia and Afghanistan, the authors examine how the application of five key practices in these (and other) contexts can create perverse incentives and inadvertently further diversion and corruption.
Keywords: Conflict Management; Afghanistan; Somalia